Two newly recorded genera and three new species of the tribe Cedusini (Hemiptera: Fulgoromorpha: Derbidae) from Korea - Rahman, Mohammad Atikur; Kwon, Yong Jung; Suh, Sang Jae (Zootaxa, 2012)
Three new derbid species, Produsa koreana sp. nov., Hauptenia palgongsanensis sp. nov. and Hauptenia tripartita sp. nov. ofthe tribe Cedusini (Hemiptera: Fulgoromorpha: Derbidae) are described and illustrated from Korea. They represent the firstrecord of the genera Produsa Szwedo, 2006 and Hauptenia Szwedo, 2006 and the tribe Cedusini in the Korean fauna. Identification keys to the known species of Produsa and Hauptenia are provided.